The effect of thyroxine and 17 beta-estradiol on vitellin synthesis in ovaries of banana prawn, Penaeus merguiensis de Man, In Vitro - Tan Swee Ling (Universiti Pertanian Malaysia, 2012)
Fragments of immature ovaries of the Banana prawn, Penaeus merguiensis, cultured in Modified Media 199 for 3 days.